An investigation into the bedrock depth in the Eskisehir Quaternary Basin (Turkey) using the microtremor method. Issue 1 (8th August 2016) - Tün, M.; Pekkan, E.; Özel, O.; Guney, Y.
Abstract: Amplification can occur in a graben as a result of strong earthquake-induced ground motion. Thus, in seismic hazard and seismic site response studies, it is of the utmost importance to determine the geometry of the bedrock depth. The main objectives of this study were to determine the bedrock depth and map the depth-to-bedrock ratio for use in land use planning in regard to the mitigation of earthquake hazards in the Eskişehir Basin. The fundamental resonance frequencies ( f r ) of 318 investigation sites in the Eskişehir Basin were determined through case studies, and the 2-D S -wave velocity structure down to the bedrock depth was explored. Single-station microtremor data were collected from the 318 sites, as well as microtremor array data from nine sites, seismic reflection data from six sites, deep-drilling log data from three sites and shallow drilling log data from ten sites in the Eskişehir Graben. The fundamental resonance frequencies of the Eskişehir Basin sites were obtained from the microtremor data using the horizontal-to vertical (H/V) spectral ratio (HVSR) method. The phase velocities of the Rayleigh waves were estimated from the microtremor data using the spatial autocorrelation (SPAC) method. The fundamental resonance frequency range at the deepest point of the Eskişehir Basin was found to be 0.23–0.35 Hz. Based on the microtremor array measurements and the 2-D S -wave velocity profiles obtained using the SPAC method, a bedrock level with an average velocity of 1300 m s −1 was accepted as the bedrock depth limit in the region. The log data from a deep borehole and a seismic reflection cross-section of the basement rocks of the Eskişehir Basin were obtained and permitted a comparison of bedrock levels. Tests carried out using a multichannel walk-away technique permitted a seismic reflection cross-section to be obtained up to a depth of 1500–2000 m using an explosive energy source. The relationship between the fundamental resonance frequency in the Eskişehir Basin and the results of deep drilling, shallow drilling, shear wave velocity measurement and sedimentary cover depth measurement obtained from the seismic reflection section was expressed in the form of a nonlinear regression equation. An empirical relationship between f r, the thickness of sediments and the bedrock depth is suggested for use in future microzonation studies of sites in the region. The results revealed a maximum basin depth of 1000 m, located in the northeast of the Eskişehir Basin, and the SPAC and HVSR results indicated that within the study area the basin is characterized by a thin local sedimentary cover with low shear wave velocity overlying stiff materials, resulting in a sharp velocity contrast. The thicknesses of the old Quaternary and Tertiary fluvial sediments within the basin serve as the primary data sources in seismic hazard and seismic site response studies, and these results add to the body of available seismic hazard data contributing to a seismic microzonation of the Eskişehir Graben in advance of the severe earthquakes expected in the Anatolian Region.